ASSESSING WATER QUALITY OF BOYALI DAM LAKE (SINOP, TURKEY) BY USING ECOLOGICAL AND STATISTICAL INDICATORS - Mutlu, Ekrem; Arslan, Naime; Tokatli, Cem (The University of Agriculture in Krakow, 2021)
Aim of the study: In the present study, the spatial – temporal variations of water quality in Boyalı Pond were analyzed. Water Quality Index (WQI) based on the World Health Organization's standards specified for drinking water, and Water Quality Control Regulations in Turkey (WQCR), as well as certain multi-statistical methods, were used in analyzing the water quality. Material and methods: Water samples were collected from 5 stations selected in the lake on monthly basis in 2019 and 30 water quality parameters were measured in total. Water Quality Index (WQI), Factor Analysis (FA), and Cluster Analysis (CA) were used in order to determine the differences between the spatial and temporal quality levels and to classify the investigated locations. Results and conclusions: According to data observed, Boyalı Dam Lake was found to have Class I and Class II water quality in general the WQI results obtained suggested that, although the water quality was found to significantly decrease in summer months, the reservoir was found to have an "A Grade – Excellent" water quality (<50) in all the months and stations analyzed here. WQI values recorded in the dam lake ranged between 16.4 and 27.8 and the detected limnologic parameters did not exceed the standards specified for drinking water in any of the investigated months and stations (<50 for WQI). As a result of FA, 3 factors explained 88.9% of total variances and as a result of CA, 2 statistical clusters were formed.
Keywords: River; Boyali Dam Lake; Trace-Elements; Area; Surface-Water; Evaluate; Metals; Water Quality Index; Cluster Analysis; Sediment; Factor Analysis; Health-Risk Assessment; 6. Clean water; 13. Climate action; 14. Life underwater